2017
DOI: 10.1021/acs.chemmater.7b01816
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trimethylaluminum in Low Temperature Atomic Layer Deposition of Silicon Nitride

Abstract: Aminosilanes are attractive precursors for atomic layer deposition of silicon oxides and nitrides because they are halide-free and more reactive than chlorosilanes. However, the deposition of silicon nitride on oxide substrates still requires relatively high temperatures. We show here that for a process involving disec-butylaminosilane and hydrazine, the insertion of Al from trimethyl aluminum allows the deposition of silicon nitride films at relatively low temperatures (250 °C). Firstprinciples calculations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…As a result, Carish can more favorably adsorb on the TMA-exposed surface than on the bare oxide surface. It is well-known from previous studies that treatment of the surface with TMA can facilitate successive adsorption of other precursors. , From DFT calculations, it is confirmed that each TMA and Carish precursor can adsorb at the unoccupied surface site in both the [C-T] and [T-C] sequences.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…As a result, Carish can more favorably adsorb on the TMA-exposed surface than on the bare oxide surface. It is well-known from previous studies that treatment of the surface with TMA can facilitate successive adsorption of other precursors. , From DFT calculations, it is confirmed that each TMA and Carish precursor can adsorb at the unoccupied surface site in both the [C-T] and [T-C] sequences.…”
Section: Resultssupporting
confidence: 52%
“…It is well-known from previous studies that treatment of the surface with TMA can facilitate successive adsorption of other precursors. 37,38 From DFT calculations, it is confirmed that each TMA and Carish precursor can adsorb at the unoccupied surface site in both the S2b in the Supporting Information). As observed in Figure 3a, the already adsorbed Carish molecules still showed two larger diketonato ligands (shown in cyan), which sterically hindered further Carish molecular adsorption.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Precursor exposure parameters were: HF (1 s pulse, Δ P = 800 mTorr), CHF 3 (5 s pulse, Δ P = 9.35 Torr), TMA (2 s pulse, Δ P = 800 mTorr), D 2 O (1 s pulse, Δ P = 300 mTorr). The TMA exposure parameters used herein are sufficient for saturation, since saturation of the hydroxyl-terminated Si(111) surface was previously demonstrated on the same home-build reactor using a 1 s TMA exposure (390 mTorr) at 250 °C …”
Section: Methodsmentioning
confidence: 99%
“…% D, Sigma-Aldrich) was used for the fluorine removal experiment to distinguish between species associated with the cleaning process and potential changes in water vapor adsorption on the spectrometer 111) surface was previously demonstrated on the same home-build reactor using a 1 s TMA exposure (390 mTorr) at 250 °C. 43 A Thermo Nicolet 6700 infrared interferometer (400−4000 cm −1 range) was connected to the reactor chamber to perform in situ FTIR measurements. All spectra were recorded in transmission mode at 4 cm −1 spectral resolution.…”
Section: Methodsmentioning
confidence: 99%